Antegrade flexible ureteroscopic lithotripsy with suctioning ureteral access sheath for large distal ureteral stones in neobladder patients: A case report - Thanakorn Pattamawalai; Kun Sirisopana; Surawach Piyawannarat; Premsant Sangkum; Wisoot Kongchareonsombat; Chinnakhet Ketsuwan (Urology Case Reports)
The use of suctioning ureteral access sheaths (sUAS) in endoscopic stone surgery provides significant advantages for retrograde procedures, including enhancing stone-free outcomes, shortening hospitalization stay, and lowering the incidence of infection. Nevertheless, in specific instances where an antegrade approach is necessary for lithotripsy, the application of these sheaths is not well established. We present the case of a patient with a neobladder and a significant ureteral calculus who was effectively treated via an antegrade approach using a flexible ureteroscope with a sUAS. This intervention enabled complete stone removal, leading to the patient's full recovery without complications.